Knowledge and adherence to osteoarthritis clinical practice guidelines among physiotherapists in Saudi Arabia: a cross-sectional study - Saad Mohammed Albogamil; Ahmed A. Ibrahim; Hisham M. Hussein; Ibrahim S. Aljulaymi; Ibrahim M. Dewir; Mostafa S. Abdelfattah (Revista Española de Educación Médica)
Background: Clinical practice guidelines (CPGs) are essential for the effective management of osteoarthritis (OA), yet their implementation among physiotherapists remains inconsistent. This study aimed to assess the knowledge and adherence of physiotherapists in Saudi Arabia to OA CPGs. Methods: A cross-sectional study was conducted using a self-administered online questionnaire targeting licensed physiotherapists in Saudi Arabia. The survey included demographic data, knowledge assessment through CPG-based statements, and a clinical vignette to evaluate adherence. Participants were categorized as Delivering, Partially Delivering, or Non-Delivering based on their alignment with CPG-recommended interventions. Results: Of 384 participants, 69% demonstrated high adherence (Delivering), while 26.3% were Non-Delivering and 4.7% Partially Delivering. Higher adherence was associated with postgraduate education, longer clinical experience, greater exposure to OA cases, and working in university or private centers. Despite 93.5% having read at least one CPG, adherence varied significantly across groups. Conclusion: While awareness of OA CPGs is high among physiotherapists, gaps in practical application persist. Targeted education, workplace support, and policy initiatives are needed to enhance adherence and improve OA care. Further research should explore barriers to guideline implementation and test tailored interventions.